Pengaruh Trading Volume Activity dan Informasi Akuntansi terhadap Harga Saham pada Perusahaan Sektor Consumer Non Cyclical Periode 2019-2023 - Satria Bagus Maulana; Mariana Mariana (Jurnal Riset Akuntansi, 2025)
This study aims to analyze the effect of trading volume activity and accounting information on stock prices. This study uses quantitative methods with a sample consisting of 23 companies in the consumer non-cyclicals sector listed on the IDX in 2019-2023. Data analysis was carried out using multiple regression techniques using SPSS software version 25. From the research conducted, the results showed that the EPS variable had an effect on stock prices, the DPS variable had an effect on stock prices, the TVA and ROCE had no effect on stock prices.